Expert Opinion on the Efficacy and Safety of Antispasmodics with a Focus on Irritable Bowel Syndrome - Bor, Serhat; Özen, Hasan; Kalkan, İsmail Hakkı and Akyüz, Filiz and Çelebi, Altay and Dinçer, Dinç and Sakin, Yusuf Serdar (Turkish Journal of Gastroenterology, 2025)
Antispasmodics are commonly used to treat irritable bowel syndrome (IBS) symptoms. They are generally regarded as safe.However, some have been found to be ineffective or not cost-effective. Marked discrepancies in the availability and formulation of antispasmodic agents across countries—ranging from the limitation to only fundamental compounds in regions such as the United States to the marketing of diverse combination products elsewhere—have generated considerable ambiguity and debate within the field. Meta-analyses show varying results on the efficacy of antispasmodics, indicating the need for further analysis. This article aims to evaluate the effectiveness of antispasmodic drugs in relieving symptoms in IBS patients. We conclude that most drugs are considered safe and effective, with pinaverium, otilonium, and peppermint oil having meta-analyses supporting their efficacy. However, there is a lack of high-quality data for drugs like alverine, trimebutine, and cimetropium, and some drugs, such as simeticone or combinations of spasmolytic agents and simeticone, have insufficient research data. Clinicians should prioritize evidence-based medicine when selecting antispasmodic agents. Cite this article as: Bor S, Özen H, Akyüz F, et al. Expert opinion on the efficacy and safety of antispasmodics with a focus on irritable bowel syndrome. Turk J Gastroenterol. 2025;36(Supp 2):S1-S38.